Analisis Manajemen Kinerja Tim Produksi pada Salah Satu PT Manufaktur di Banten - Vini Qonita; Rahmah Wati; Aprilya Fitriani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract. This study aims to analyze the implementation of performance management and production team management in a manufacturing company located in Banten, Indonesia. The focus of the research includes examining the processes of performance planning, implementation, and evaluation, as well as identifying the supporting and inhibiting factors and the efforts undertaken to improve production team performance. This study employs a qualitative approach using a descriptive method. Data were collected through semi-structured interviews conducted directly with the Production Planning and Inventory Control (PPIC) Manager, who served as the primary informant, as well as through relevant company documentation. Data analysis was carried out using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings indicate that the company has implemented a structured performance management system by utilizing Key Performance Indicators (KPIs), a rating system, 360-degree feedback, and self-assessment as performance evaluation instruments. Factors that may hinder performance include inventory inaccuracies, delays in interdepartmental information exchange, human errors, and logistical constraints. Meanwhile, supporting factors in the implementation of performance management include clearly defined work targets, well-documented Standard Operating Procedures (SOPs), and the consistent application of reward and punishment systems. To improve performance, the company has undertaken several initiatives, including the digitalization of information systems, employee competency development through training programs, and the strengthening of coordination among departments. The study concludes that a systematic performance management implementation can enhance the effectiveness of production teams and support the achievement of organizational goals.